2014
DOI: 10.1371/journal.pone.0086155
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease Is Characterized by “Double Trouble” Higher Pulse Pressure plus Night-Time Systolic Blood Pressure and More Severe Cardiac Damage

Abstract: BackgroundHypertension plays a key role in chronic kidney disease (CKD), but CKD itself affects the blood pressure (BP) profile. The aim of this study was to assess the association of BP profile with CKD and the presence of cardiac organ damage.MethodsWe studied 1805 patients, referred to our Hypertension Centre, in whom ABPM, blood tests, and echocardiography were clinically indicated. The glomerular filtration rate was estimated (eGFR) using the MDRD equation and CKD was defined as eGFR<60 mL/min/1.73 m2. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
1
24
1
Order By: Relevance
“…That study demonstrated also a relationship between prevalence of CKD and non-dipping pattern of hypertension. It indicated that CKD had direct influence on circadian BP profile [122]. That finding was in agreement with former study by Farmer et al, who reported more frequent predominance of non-dipping in subjects with CKD than in controls with essential hypertension [123].…”
Section: Chronic Kidney Diseasesupporting
confidence: 91%
See 1 more Smart Citation
“…That study demonstrated also a relationship between prevalence of CKD and non-dipping pattern of hypertension. It indicated that CKD had direct influence on circadian BP profile [122]. That finding was in agreement with former study by Farmer et al, who reported more frequent predominance of non-dipping in subjects with CKD than in controls with essential hypertension [123].…”
Section: Chronic Kidney Diseasesupporting
confidence: 91%
“…According to National Kidney Foundation, elevated level of BP may be either a consequence or a cause of chronic kidney disease (CKD) defined as a presence of, for 3 months or more, at least one of the following criteria: kidney damage or/and GFR < 60 ml/min/1,73 m 2 [121]. Among 264 patients with CKD involved in investigation by Fedecostante et al, approximately all (97.8%) were hypertensive [122]. That study demonstrated also a relationship between prevalence of CKD and non-dipping pattern of hypertension.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…Others and we have observed that in a very elderly population there was only a weak correlation between estimated GFR and indices of cardiac structure and function, suggesting that extracardiac factors such as arterial stiffening may be mediating this relationship [14]. Hypertensive CKD patients have both increased LV mass as compared to non-CKD patients and increased PP, which correlates strongly with end-organ damage including LVH [15]. Tripepi et al [16] demonstrated that increased PP was one of the strongest correlates with increased LV mass associated with aging in hemodialysis patients, supporting an important hemodynamic role for increased PP in the development of LVH and CKD in the elderly.…”
Section: Hemodynamic Factorsmentioning
confidence: 97%
“…Patients with CKD also tend to have a nondipping pattern possibly due to defective natriuresis during daytime or to altered sympathetic activity [15]. In the study by Fedecostante et al [15],age was independently associated with a nondipping pattern, confirming that this pattern may be important in the development of LVH and CKD in the elderly. Presumably, an increased use of ambulatory blood pressure monitoring and improving blood pressure control at nighttime would help reduce LVH and CKD in the elderly.…”
Section: Hemodynamic Factorsmentioning
confidence: 99%
“…There is also emerging data looking at various measures of HTN beyond casual BP measurements, including parameters of ABPM as well as pulse pressure and non-invasive measurements of central BP, and how they relate to clinical outcomes [46][47][48]. Some evidence suggests that these measures may be more accurate prognostic indicators for such outcomes as cerebrovascular events, cardiovascular events, and CKD progression [49,50]. More research is clearly needed in the pediatric population to elucidate the best BP target that will both minimize CKD progression and also future cardiovascular disease risk.…”
Section: Goals Of Therapymentioning
confidence: 99%